EVALUASI IKLIM KESELAMATAN KERJA DIVISI PRODUKSI BERBASIS INSTRUMEN KUESIONER NOSACQ-50 DI PT MNM - Ma'ruf, Najah Maulana; Mahbubah, Nina Aini (Fakultas Teknik, Universitas Riau Kepulauan, 2024)
One way to improve occupational safety and health is to establish a culture of safety within the workplace. PT MNM is an international company that has established a safety culture through management and employee commitment. This research aims to evaluate the work safety climate in the bagging division using a multiple linear regression based on a statistical approach. NOSACQ-50 was used as a questionnaire instrument, accompanied by seven independent and one dependent variable. The population involved in this research was 36 Bagging workers in the Production Department. Once the validity, reliability, and normality tests were conducted, the data was calculated using multiple linear statistical hypothesis tests. The research results show that four independent variables significantly influence work safety climate. Namely management empowerment (X1), safety management empowerment (X2), safety management justice (X3), communication and work safety training, and trust in competition for work safety from colleagues (X6). In addition, the three remaining dimensions whose results do not significantly influence the work safety climate. Namely variables of worker commitment to safety (X4), worker safety priorities and not tolerating danger risks (X5), and trust in the effectiveness of the safety system (X7). The final results show that three insignificant variables can improve safety culture.